2014
DOI: 10.4238/2014.march.24.6
|View full text |Cite
|
Sign up to set email alerts
|

Significance of SODD expression in childhood acute lymphoblastic leukemia and its influence on chemotherapy

Abstract: ABSTRACT. This study explored the clinical significance of silencer of death domain (SODD) expression in childhood acute lymphoblastic leukemia (ALL) and its influence on chemotherapy as well as the effect of SODD expression on apoptosis of leukemic cells. The expression of SODD proteins in different ALL groups was determined by immunocytochemistry. The SODD RNAi-interfering plasmid was constructed and transferred to Jurkat cells, and the effects of SODD expression on cell proliferation and apoptosis were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…In our comparison of PL versus ML, the top two differentially abundant proteins were bcl‐2‐associated athanogene 4 (BAG4) and insulin‐like growth factor‐1 receptor (IGF1R). BAG4, also called silencer of death domains (SODD), has been shown to have crucial roles in inhibiting apoptosis . Even though no pathway was annotated, IGF1R was also enriched in GO terms associated with apoptosis, such as negative regulation of apoptotic process, which implied that anti‐apoptotic activities may play an important role in the luteal phase.…”
Section: Discussionmentioning
confidence: 99%
“…In our comparison of PL versus ML, the top two differentially abundant proteins were bcl‐2‐associated athanogene 4 (BAG4) and insulin‐like growth factor‐1 receptor (IGF1R). BAG4, also called silencer of death domains (SODD), has been shown to have crucial roles in inhibiting apoptosis . Even though no pathway was annotated, IGF1R was also enriched in GO terms associated with apoptosis, such as negative regulation of apoptotic process, which implied that anti‐apoptotic activities may play an important role in the luteal phase.…”
Section: Discussionmentioning
confidence: 99%
“…This burden is partly due to uncontrolled cell proliferation and poor response to chemotherapy in adult patients [4]. Leukemic cells abnormally express numerous genes that are associated with proliferation and apoptosis compared to normal hematopoietic cells, and these genes are thought to be the main cause of drug resistance [5]. An examination of abnormally expressed genes in leukemic cells, and of the pathogenic mechanisms associated with these genes, would therefore have great value for the development of targeted therapies.…”
Section: Introductionmentioning
confidence: 99%
“…BAG4 influences the growth of several types of cancer, such as pancreatic [24] , ovarian [25] , and breast cancer [26] . Additionally, Cisterne [27] and Tao [28] found that in acute lymphoblastic leukemia, BAG4/SODD plays the important role in various processes, including apoptosis and the chemotherapy sensitivity. We predicted and verified that BAG4 is a direct targets of miR-1-3p and may be a key factor in BEZ235-induced apoptosis.…”
Section: Wwwchinapharcom Deng L Et Almentioning
confidence: 99%